2013
DOI: 10.1017/s0025315413001689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of periotic–timpanic bone complex ofSotalia guianensis(Cetacea: Delphinidae) as tool in identification of geographic variations

Abstract: Morphometric characteristics of the periotic -timpanic bone complex in the middle ear of cetaceans, are effective characteristics in evaluating systematics. However, they have not been used for studies of geographic variation regarding dolphins of the genus Sotalia. This study aimed to compare the periotic -timpanic of Sotalia guianensis from four distinct locations, considered here as different operational taxonomic units, Amapá/Pará (AM/PA), Maranhão/Piauí (MA/PI), Ceará (CE), and Rio de Janeiro (RJ), using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…This might explain the fact that no variation could be revealed in the transverse view. Geographical differences in the middle ear of Guiana dolphins ( Sotalia guianensis ) were found in a recent study between the coasts of northern and south-eastern Brazil, which are consistent with population genetic structure 39 . The traditional morphometrics of the T-P bone complex revealed to be an efficient tool to identify geographic variations in this species.…”
Section: Discussionsupporting
confidence: 80%
“…This might explain the fact that no variation could be revealed in the transverse view. Geographical differences in the middle ear of Guiana dolphins ( Sotalia guianensis ) were found in a recent study between the coasts of northern and south-eastern Brazil, which are consistent with population genetic structure 39 . The traditional morphometrics of the T-P bone complex revealed to be an efficient tool to identify geographic variations in this species.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, Arcoverde et al (2014) found consistent morphological differences in the middle ear of Sotalia guianensis between the coasts of northern and south-eastern Brazil, consistent with population genetic structure.…”
supporting
confidence: 76%
“…Despite the apparent lack of physical boundaries in the marine environment, geographical differences, often at surprisingly fine spatial scales, are reflected in the morphology, phenology, behavioural ecology, diet and ultimately population genetic structure of the various marine mammals that were once thought to freely roam the oceans. Thus, Arcoverde et al (2014) found consistent morphological differences in the middle ear of Sotalia guianensis between the coasts of northern and south-eastern Brazil, consistent with population genetic structure.…”
mentioning
confidence: 58%
“…Skull analyses from the north, northeast and southeast have been demonstrated a complete separation between Pará and Rio de Janeiro populations, and a partial separation between Pará, Maranhão and Piauí 98 . Analyses of the periotic-tympanic bone complex of three Brazilian regions also reported geographic variations 99 .…”
Section: Discussionmentioning
confidence: 98%